2021
DOI: 10.1002/icd.2221
|View full text |Cite
|
Sign up to set email alerts
|

The role of mother's prenatal substance use disorder and early parenting on child social cognition at school age

Abstract: This prospective longitudinal study examined how maternal prenatal substance use disorder (SUD) and early mother–infant interaction quality are associated with child social cognition (emotion recognition and mentalization) at school age. A sample of 52 poly‐substance‐using mothers receiving early interventions and 50 non‐users, along with their children, was followed from pregnancy to school age. First‐year mother–infant interaction quality was measured with EA scales. At school age, child facial emotion recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…This interpretation is in line with prior findings that children who experienced physical abuse (i.e., trauma accompanied by parental emotion dysregulation, inconsistency, and hostility) were highly adept at detecting subtle emotional cues (Pollak and Sinha, 2002). Similarly heightened emotion recognition and threat detection has been observed in children exposed to parental depression (Lopez-Duran et al, 2013) and substance use (Flykt et al, 2021). Overall, such hypersensitivity may help individuals predict and thereby cope with inconsistent, unpredictable, dysregulated, or confusing caregiving behavior exhibited by mothers experiencing mental illness.…”
Section: Discussionsupporting
confidence: 89%
“…This interpretation is in line with prior findings that children who experienced physical abuse (i.e., trauma accompanied by parental emotion dysregulation, inconsistency, and hostility) were highly adept at detecting subtle emotional cues (Pollak and Sinha, 2002). Similarly heightened emotion recognition and threat detection has been observed in children exposed to parental depression (Lopez-Duran et al, 2013) and substance use (Flykt et al, 2021). Overall, such hypersensitivity may help individuals predict and thereby cope with inconsistent, unpredictable, dysregulated, or confusing caregiving behavior exhibited by mothers experiencing mental illness.…”
Section: Discussionsupporting
confidence: 89%
“…Just as with smoking, it is difficult to pry apart the biological effect and family environment. Flykt and colleagues found that severe maternal substance use disorder predicted impaired emotion recognition in offspring (Flykt et al, 2021). However, this deficit was moderated by the quality of the mother–child relationship in infancy (Flykt et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Flykt and colleagues found that severe maternal substance use disorder predicted impaired emotion recognition in offspring (Flykt et al, 2021). However, this deficit was moderated by the quality of the mother–child relationship in infancy (Flykt et al, 2021). Our finding that the father's post-secondary qualification is protective against threatening others suggests that both parent relationships are important.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that mothers who use substances are likely to be less emotionally available with their children. Early maternal substance use has been found to predict lower child emotion regulation (Punamaki et al, 2021) and social cognition (Flykt et al, 2021) at school age. Furthermore, using the EA-Z, Frigerio et al (2019) found that substance-using mothers were most likely to be complicated, depressed mothers most likely to be detached, and nonat-risk mothers most likely to be emotionally available in their emotional attachments.…”
Section: Maternal Substance Use Disordermentioning
confidence: 99%